Pengaruh Pengetahuan Keuangan, Teman Sebaya, dan Parental Income terhadap Perilaku Keuangan dengan Self-Control sebagai Moderasi - Putri Cahyani; Rochmawati Rochmawati (Universitas Negeri Padang, 2021)
Abstract : Analyzing the effect of financial knowledge, friends of the same age, and parental income on financial behavior with self-control as a moderating variable is the purpose of this research. Quantitative research is a type of research used in this study. The research sample was determined by purposive sampling technique totaling 100 students. Data analysis techniques used Structural Equation Modeling (SEM). Data collection techniques used were test and questionnaires. The result of this research is that financial knowledge can’t significantly influence financial behavior of students. Peer pressure, parental income, and self control have a significant on student financial behavior. Self control cann’t moderate financial knowledge on financial behavior, but it can moderate peer moderation on financial behavior. Self control does not moderate parental income on student financial behavior.